Optimal network selection algorithms under the multi-network coexistence environment based on attribute decision. Issue 2 (28th February 2020) - Ma, Chungeng; Hou, Lixia; Ma, Wenjing
In order to perform optimal network selection under the multi-network coexistence environment and realise adaptive switching of network to improve the stability of network transmission, an optimal network selection algorithm under the multi-network coexistence environment based on attribute decision is proposed. In this algorithm, a network channel distribution model under the multi-network coexistence environment is constructed; the adaptive link priority control method is adopted to perform network channel switching under the multinetwork coexistence environment, and a dynamic scheduling model for network transmission channel under multi-network coexistence is constructed. Simulation results show that when this proposed method is adopted for optimal network selection under the multi-network coexistence environment, the channel equalisation of network transmission and network stability are good and the output bit error rate is low.